2015
DOI: 10.1097/sla.0000000000001114
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcomes After Initial Presentation of Diverticulitis

Abstract: Eighty-five percent of emergent diverticulitis patients do not recur after initial medical treatment. However, in view of significantly worse outcomes associated with diverticulitis recurrence, resection should be strongly considered for diverticulitis patients older than 50 years or those who present with a complicated clinical picture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 35 publications
3
56
0
12
Order By: Relevance
“…There are multiple classification systems for complicated diverticulitis, of which the Hinchey Classification (Table 1) is most widely used [11]. Morris et al [12] performed a systematic review of diverticulitis, including the natural history, and illustrated their findings using a hypothetical cohort of 1,000 patients, which is reproduced, with permission, in Figure 1.This is consistent with a population-based Californian study in which 84% of patients with acute diverticulitis are successfully managed conservatively without them having to experience a second episode [13]. The outcomes of recurrent episodes of acute diverticulitis are particularly relevant for planning long-term management.…”
Section: Introductionsupporting
confidence: 57%
“…There are multiple classification systems for complicated diverticulitis, of which the Hinchey Classification (Table 1) is most widely used [11]. Morris et al [12] performed a systematic review of diverticulitis, including the natural history, and illustrated their findings using a hypothetical cohort of 1,000 patients, which is reproduced, with permission, in Figure 1.This is consistent with a population-based Californian study in which 84% of patients with acute diverticulitis are successfully managed conservatively without them having to experience a second episode [13]. The outcomes of recurrent episodes of acute diverticulitis are particularly relevant for planning long-term management.…”
Section: Introductionsupporting
confidence: 57%
“…The distinction between complicated and uncomplicated disease has been routinely applied to colonic diverticulitis for many years [1]. Numerous classifications have been developed to categorize the complicated disease [2] and its surgical treatment [3], but when it comes to symptomatic uncomplicated diverticular disease, it is still difficult to give a clear definition and provide the correct surgical indication [4]. Some authors have described symptomatic uncomplicated diverticular disease as the presence of active disease without episodes of colonic perforation and therefore without the development of pericolic abscesses [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…But surgery still seems to play an important role. For example, Rose et al [68] found recently that the mortality rate of delayed elective surgical intervention after the first episode of emergent diverticulitis was 0.3% compared with 4.6% for emergent resection during a second episode. Currently, the main question is when elective resection has to be advised.…”
Section: Surgerymentioning
confidence: 97%